HOW ABOUT USING A METAPHOR FOR DESIGN THINKING AND CREATIVITY IN INTERIOR ARCHITECTURAL DESIGN STUDIO? - Duzgun, Ebru; Bekdas, Hande Duzgun (IATED-INT ASSOC TECHNOLOGY EDUCATION & DEVELOPMENT, 2019)
Generally, the lack of disconnection and creativity in transforming the abstract into concrete is an important problem area in the design education. For this reason, conceptual thinking is one of the most creative and linking design methods applied recently. In this context, Metaphors, which by definition are especially suitable for imaginary and different thinking, offer a variety of possibilities for changing and transforming concepts, by enabling to approach design problems from surprising perspectives. Metaphors, which have also an important place in the interior design of architecture recently, play a key role both in analysis and synthesis stages. And also metaphors have a simplifying and guiding function in increasing the readability, forming the relationship of knowledge networks, interpretating, and enabling to produce innovative ideas during the design process. This paper aims of studying the potential of metaphors as a design tool for the interior architecture during the early stages of design approach. The study includes the findings of the series of studies involving interior architectural design students who were asked to use a metaphor in the context of their specific project concepts with their own design experience. As a result, the study explores for different ways to create a level of cognitive awareness in the problem solving stage in design and to create goals for more creative and innovative processes.
Keywords: Metaphor; Interior Design; Design Thinking; Abstraction; Creativity; ART; Education & Educational Research